Trust or attention? Medialization of science revisited. (April 2022) - Weingart, Peter
The article traces the intensifying media orientation of universities and research organizations first by referring to early diagnoses of the spread of mutual observation and attention seeking as defining societies after WWII. This development provides the background for the unlikely, yet massive turn of scientific organizations to the general public, the media and more recently social media. Details are analyzed on the interactional, organizational and systems levels, and are followed with a focus on the reasons motivating universities. A closer look reveals the self-referentiality of institutional communication deriving its rationale from 'imagined publics'. The politically sponsored 'engagement of the public' has been derailed to become marketing, branding and public relations exercises. The unintended consequences of the establishment of communication units and the blurring of science communication and persuasion are conflicts between faculty and management and possibly a loss of trust in science.